Cross-cultural adaptation of the Job Insecurity Scale (JIS) in Brazil and cross-national analysis of Job Insecurity effects in Brazil and Spain - José Antonio Llosa; Esteban Agulló-Tomás; Sara Menéndez-Espina; Camila Teixeira Heleno; Livia de Olivera Borges (BMC Psychology, 2023)
Abstract Background Job flexibilisation has increased interest in job insecurity and its consequences. Job insecurity, understood as a fear of losing employment, is linked to a deterioration of mental health, social relations or job satisfaction. Its study has been developed primarily in Europe, in the absence of validated psychometric scales in the Latin American context. To bridge this knowledge gap, the aim of this study is to cross-culturally adapt the Job Insecurity Scale (JIS) in Brazil, and secondly, to establish a cross-national analysis between people employed in Brazil and Spain. Methods As criteria for the sample, people with formally established employment in Brazil and Spain were selected. For the scale adaptation process, a sequence of EFA, CFA and validity tests are carried out, as well as a multigroup invariance according to the gender variable. The cross-national comparison compares the effect sizes of affective and cognitive job insecurity on the mental health variable measured with the GHQ-28 scale in both countries. Results 1165 employed people participate in the study, of whom 573 reside in Brazil and 592 in Spain. The results of the scale adaptation show that the JIS is suitable for use in the Brazilian employment context. The scale offers a factorialisation in two dimensions (affective and cognitive) (CFI = 0.993; TLI = 0.987; RMSEA = 0.04; SRMR = 0.049; GFI = 0.999; NFI = 0.980) with good reliability (ω > 0.84). The cross-national comparison shows that job insecurity has a greater weight in explaining the mental health of the employed population in Brazil than in Spain, which is related to higher indicators of job insecurity in the Brazilian context. Conclusions With this validation we now have a validated scale of job insecurity validated for the Brazilian context. The comparison between countries shows the need to establish these analyses, since the behaviour of the phenomenon is different in the contexts studied.